Prediction of Flexural Stiffness of Wooden Beams with Cross-sectional Loss that Are Reinforced with Screwed Steel Plate Based on Numerical Simulation - Jardim, Pedro I. L. G.; Morales, Elen A. M. [UNESP]; Panzera, Tulio H.; Mascarenhas, Fernando J. R.; Araujo, Victor A.; Santos, Herisson F.; Faustino, Emerson; Almeida, Diego H.; Lahr, Francisco A. R.; Christoforo, Andre L. (North Carolina State Univ Dept Wood & Paper Sci, 2023)
As a biodegradable material, wood is subject to deterioration if proper conservation techniques are not observed. Thus, several buildings, especially those of historical heritage, present pathological manifestations that can cause accidents. The interventions in these constructions must be planned to maintain the original elements and the aesthetics of the environment, with the indication of fixing additional elements in the degraded structure. The modification of the section of structural elements is commonly observed in the literature; however, few studies have been intended to analyze the effects of reinforcement in these geometrically discontinuous elements. Furthermore, the use of screwed steel plates guarantees greater ease of execution, even though it is not yet a method that has been well explored in the scientific literature. The objective of this study was to propose an equation for estimating the flexural stiffness of wooden beams with loss of cross-section that are then reinforced with screwed steel plates using a regression model. The considered variables correlated the elastic modulus of the wood and the reinforcement, the configuration of the defect, and the reinforcement. It was possible to identify that the properties of the wood and the position of the defect were variables with a significant impact on the stiffness of the reinforced beam.
Keywords: Bending stiffness; Structural recovery; Reinforced timber structures; Screwed steel plate